2015
DOI: 10.1016/j.dhjo.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis isn't enough: Understanding the connections between high health care utilization, chronic conditions and disabilities among U.S. working age adults

Abstract: Background Under the ACA, new programs are being developed to enhance care coordination and reduce healthcare costs among people with chronic conditions, disabilities, and high utilization of healthcare. However, the relationships between these groups are not well understood. Objectives Our aims were to (1) identify high utilizers of healthcare in the U.S. working-age (18-64) population, (2) examine the overlap between this group and people with chronic conditions and/or disabilities, (3) identify predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Secondary data sources rarely include information on environmental supports and barriers; therefore, disability is typically assessed through self-report of functional ability and participation restrictions when such data are available [e.g. 2, 21–27]. Research examining specific conditions associated with self-report of functional or participation limitations has found that common underlying conditions include arthritis, back problems, other musculoskeletal problems, pulmonary problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary data sources rarely include information on environmental supports and barriers; therefore, disability is typically assessed through self-report of functional ability and participation restrictions when such data are available [e.g. 2, 21–27]. Research examining specific conditions associated with self-report of functional or participation limitations has found that common underlying conditions include arthritis, back problems, other musculoskeletal problems, pulmonary problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using pooled secondary data from the 2006–2008 Medical Expenditure Panel Survey, we conducted detailed analyses of the relations between high healthcare utilization, functional limitations and chronic conditions. 42 In order to identify working age individuals with (and without) one or more chronic conditions, we used the HCUP chronic condition list (AHRQ) which specifies health and mental health conditions expected to last a year or more by ICD-9 code. We identified persons with limitations on the basis of the functional measures provided in MEPs.…”
Section: Resultsmentioning
confidence: 99%
“…Other disability types were included as a control measure because a substantive body of literature has shown a significant overlap between these disability types and poor health and healthcare outcomes. 15,16 Models including other disability types revealed few differences (details available upon request). We chose to present the models controlling for other disability types to more conservatively assess the impact of CD on outcomes.…”
Section: Discussionmentioning
confidence: 99%